The best American magazine writing 2016 - Holt, Sid; American Society of Magazine Editors (New York : Columbia University Press, 2016)
Features articles that were judged finalists and winners in the National Magazine Awards, presenting works from leading journalists on such topics as reparations, Internet sexual harassment, the public humiliation complex, and the college rape crisis.
Frontmatter -- Contents -- Introduction: Going Native: An Eight-Minute Read -- Acknowledgments -- Fixing the System: An Interview with President Obama on Prison Reform -- What Is Code? If You Don't Know, You Need to Read This -- The New American Slavery and "All You Americans Are Fired" -- "Pregnant? Scared? Need Options? Too Bad" -- "My Nurses Are Dead, and I Don't Know If I'm Already Infected" -- Purgatory -- The Really Big One -- An Unbelievable Story of Rape -- A Visit to the Sweat Lodge and Santa Muerte, Full of Grace and Stop Sending me Jonathan Franzen Novels -- Down for the Count and The King Has Spoken and The Power of Sight -- The Friend -- How It Feels -- Permissions -- List of Contributors.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: American prose literature -- 21st century; Journalism -- Awards -- United States; Prose américaine -- 21e siècle.; LANGUAGE ARTS & DISCIPLINES -- Journalism; American prose literature; Journalism -- Awards; United States; 2000-2099